The Glossopharyngo-Cochlear Triangle—Part I: Quantitative Anatomic Analysis of High-Riding Posterior Inferior Cerebellar Artery Aneurysms Exposed Through the Extended Retrosigmoid Approach. Issue 3 (29th December 2020) - Zhao, Xiaochun; Tayebi Meybodi, Ali; Naeem, Komal; Belykh, Evgenii; Labib, Mohamed A; Baranoski, Jacob F; Catapano, Joshua S; Mascitelli, Justin R; Preul, Mark C; Lawton, Michael T
Abstract: BACKGROUND: An extended retrosigmoid approach can offer sufficient space for clip reconstruction of some high-riding posterior inferior cerebellar artery (PICA) aneurysms. OBJECTIVE: To quantitatively investigate the glossopharyngo-cochlear triangle (GCT) and anatomic structures within it. METHODS: Extended retrosigmoid craniotomies were performed on 10 sides of cadaveric heads, and the GCT was identified in each specimen. The length of the base and the area of the GCT were measured. The depth of the vertebrobasilar system and the abducens nerve to the GCT were measured. The proximal and distal exposable and controllable points on the vertebrobasilar system were identified. Two imaging-based patient selection algorithms are provided using the lengths from those points to the vertebral artery dural entry point and the superoinferior distances from those points to the inferior edge of the foramen magnum. Other factors related to accessibility via the GCT were investigated. RESULTS: The mean (standard deviation [SD]) area of the GCT was 45.7 (12.55) mm 2 . The mean (SD) depth of the abducens nerve was 14.3 (1.42) mm. The mean (SD) superoinferior distances from the foramen magnum to those points were 23.1 (7.39), 24.7 (8.25), 30.0 (9.56), and 32.6 (7.79) mm, respectively. The lower segment of the vertebrobasilar system was more superficial in the setting of a high-lying vertebrobasilar junction (VBJ) than a low-lying VBJ. CONCLUSION: We describe the GCT in an extended retrosigmoid approach for high-riding PICA aneurysms and evaluate the spatial relationship of the neurovascular structures within it. Two potential algorithms are offered for preoperative patient selection.